Determinants of arrears in the municipal savings banks, rural savings banks and EDPYMES of Peru - Calle Arancibia, Margarita Elluz (2020)
The objective this paper is analyzed the relationship between the administration of the working capital and the profitability of assets of the companies of the Peruvian agricultural sector of the period 2009-2018. Through an econometric model it was obtained that the ROA is significantly related to the PPI (p <0.05), PPC (p <0.05) and PPP (p <0.10). This indicates that the profitability of these companies depends on the application of appropriate policies regarding their inventories, accounts receivable and accounts payable.